The Influence of Organizational Support and Citizen Behavior on Job Performance of New Energy Enterprises: Mediating Effects of Psychological Capital - You Zhang; Lu Zhang; Meng Zhang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Job performance is an essential element for the success of an organization and economic growth. The present study investigates the impact of organizational support and organizational citizen behavior on the job performance of new energy enterprises. The goal also includes an examination of mediating effects of psychological capital among the nexus of organizational support, organizational citizen behavior and job performance of new energy enterprises. The data was obtained by using the questionnaires from the employees of energy enterprises, and the data were analyzed by employing the smart-PLS software. The results revealed that organizational support and organizational citizen behavior have a positive association with the job performance of energy enterprises. The outcomes also exposed that the psychological capital positively mediates among the nexus of organizational support, organizational citizen behavior, and job performance of energy enterprises. These outcomes would provide guidelines to regulators of any organization that they should develop valuable policies that enhance the job performance that could lead the organization towards success.